Relativistic forces in special and general relativity - Sfarti, Adrian (Cambridge Scholars Publisher, 2022)
This book presents a generalization of transforms from the frames co-moving with an accelerated particle for uniform circular or linear motion into an inertial frame of reference. The solutions presented here will be of great interest for real-time applications because earth-bound laboratories are inertial only in approximation. The motivation behind this is that real life applications include accelerating and rotating frames with arbitrary orientations more often than the idealized case of inertial frames. The book is divided into three main sections: the first deals with the theory of dynami.